Peningkatan Kemampuan Pemecahan Masalah Melalui Model Pembelajaran Problem Based Learning Menggunakan Pendekatan Teaching at the Right Level SDN 127 Palembang - Monica, Fitria; Iswahyuni, Iswahyuni; Lestari, Novi; Saparini, Saparini; Dewi, Eka Aprilia (SJEE (Scientific Journals of Economic Education), 2025)
The aim of this research is to improve the problem solving abilities of students in class IVD at SD Negeri 127 Palembang through the application of the Problem Based Learning (PBL) learning model with the Teaching at the Right Level (TaRL) approach. This type of research is classroom action research with research subjects of 30 class IVD students at SD Negeri 127 Palembang. The data collection techniques used were observation, tests, interviews and field notes. This research was conducted in 2 cycles on 30 July 2024 and 7 August 2024. Before conducting classroom research, an initial test was carried out to determine students' problem-solving abilities. From the initial test results, it was found that the average score for students' problem solving abilities was 60.72. In cycle I the average value of students' problem solving abilities increased to 67.74. There are 19 students who have scored above the KKM, namely ≥75, while 11 others still have scores below the KKM. In cycle II the average value of students' problem solving abilities was 80.67. There are 25 students who have scored above the KKM, namely ≥75, while 5 others still have scores below the KKM. Thus it can be concluded that the application of the Problem Based Learning (PBL) learning model with the Teaching at the Right Level (TaRL) approach can improve students' problem solving abilities.